Optimal portfolio management when stocks are driven by Mean-Reverting Processes - Mbigili, Lusungu Julius (University of Dar es Salaam, 2024)
A dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science (Mathematical Modelling) of the University of Dar es Salaam